A Note on the Discrete Spectrum of Gaussian Wells (I): The Ground State Energy in One Dimension - G. Muchatibaya; S. Fassari; F. Rinaldi; J. Mushanyu (Advances in Mathematical Physics)
The ground state energy E0(λ) of Hλ=-d2/dx2-λe-x2 is computed for small values of λ by means of an approximation of an integral operator in momentum space. Such an approximation leads to a transcendental equation for which ϵ0(λ)=|E0(λ)|1/2 is the root.